Improving accuracy of direct and maternal genetic effects in genomic evaluations using pooled boar semen: a simulation study - Maiorano, Amanda M. [UNESP]; Assen, Alula; Bijma, Piter; Chen, Ching-Yi; Vasconcelos Silva, Josineudson Augusto [UNESP]; Herring, William O.; Tsuruta, Shogo; Misztal, Ignacy; Lourenco, Daniela A. L. (Oxford Univ Press Inc, 2019)
Pooling semen of multiple boars is commonly used in swine production systems. Compared with single boar systems, this technique changes family structure creating maternal half-sib families. The aim of this simulation study was to investigate how pooling semen affects the accuracy of estimating direct and maternal effects for individual piglet birth weight, in purebred pigs. Different scenarios of pooling semen were simulated by allowing the same female to mate from 1 to 6 boars, per insemination, whereas litter size was kept constant (N = 12). In each pooled boar scenario, genomic information was used to construct either the genomic relationship matrix (G) or to reconstruct pedigree in addition to G. Genotypes were generated for 60,000 SNPs evenly distributed across 18 autosomes. From the 5 simulated generations, only animals from generations 3 to 5 were genotyped (N = 36,000). Direct and maternal true breeding values (TBV) were computed as the sum of the effects of the 1,080 QTLs. Phenotypes were constructed as the sum of direct TBV, maternal TBV, an overall mean of 1.25 kg, and a residual effect. The simulated heritabilities for direct and maternal effects were 0.056 and 0.19, respectively, and the genetic correlation between both effects was -0.25. All simulations were replicated 5 times. Variance components and direct and maternal heritability were estimated using average information REML. Predictions were computed via pedigree-based BLUP and single-step genomic BLUP (ssGBLUP). Genotyped littermates in the last generation were used for validation. Prediction accuracies were calculated as correlations between EBV and TBV for direct (acc(direct)) and maternal (acc(mat)) effects. When boars were known, acc(direct) were 0.21 (1 boar) and 0.26 (6 boars) for BLUP, whereas for ssGBLUP, they were 0.38 (1 boar) and 0.43 (6 boars). When boars were unknown, acc(direct) was lower in BLUP but similar in ssGBLUP. For the scenario with known boars, acc(mat) was 0.58 and 0.63 for 1 and 6 boars, respectively, under ssGBLUP. For unknown boars, acc(mat) was 0.63 for 2 boars and 0.62 for 6 boars in ssGBLUP. In general, acc(direct) and acc(mat) were lower in the single-boar scenario compared with pooled semen scenarios, indicating that a half-sib structure is more adequate to estimate direct and maternal effects. Using pooled semen from multiple boars can help us to improve accuracy of predicting maternal and direct effects when maternal half-sib families are larger than 2.
Keywords: genomic prediction; maternal ability; multiple sire; prediction accuracy